Implementing tobacco use treatment guidelines in community health centers in Vietnam. (December 2015) - Shelley, Donna; VanDevanter, Nancy; Cleland, Charles; Nguyen, Linh; Nguyen, Nam
Abstract Background Vietnam has a smoking prevalence that is the second highest among Southeast Asian countries (SEACs). According to the World Health Organization (WHO), most reductions in mortality from tobacco use in the near future will be achieved through helping current users quit. Yet, largely due to a lack of research on strategies for implementing WHO-endorsed treatment guidelines in primary care settings, services to treat tobacco dependence are not readily available to smokers in low middle-income countries (LMICs) like Vietnam. The objective of this study is to conduct a cluster randomized controlled trial that compares the effectiveness of two system-level strategies for implementing evidence-based guidelines for the treatment of tobacco use in 26 public community health centers (CHCs) in Vietnam. Methods/Design The current study will use a cluster-randomized design and multiple data sources (patient exit interviews, provider and village health worker (VHW) surveys, and semi-structured provider/VHW interviews) to study the process of adapting and implementing clinical practice guidelines in Vietnam and theory-driven mechanisms hypothesized to explain the comparative effectiveness of the two strategies for implementation. CHCs will be randomly assigned to either of the following: (1) training plus clinical reminder system (TC) or (2) TC + referral to a VHW (TCR) for three in person counseling sessions. The primary outcome is provider adherence to tobacco use treatment guidelines. The secondary outcome is 6-month biochemically verified smoking abstinence. Discussion The proposed implementation strategies draw on evidence-based approaches and a growing literature that supports the effectiveness of integrating community health workers as members of the health care team to improve access to preventive services. We hypothesize that the value of these implementation strategies is additive and that incorporating a referral resource that allows providers to delegate the task of offering counseling (TCR) will be superior to TC alone in improving delivery of cessation assistance to smokers. The findings of this research have potential to guide large-scale adoption of promising strategies for implementing and disseminating tobacco use treatment guidelines throughout the public health system in Vietnam and will serve as a model for similar action in other LMICs. Trial registration NCT01967654